Simulando efeitos de fusões sobre equilíbrio de preços: um estudo para o mercado brasileiro de automóveis - Silva, Vitor Hugo Miro Couto (2009)
This dissertation presents an analysis of mergers simulation on the Brazilian automobile market. The central objective is computing the effects of a merger in the equilibrium price. Postmerger equilibrium outcomes are simulated under some assumptions on the demand and the supply sides. This study applies a Nested Logit model to model the demand, as proposed by Berry (1994). From the demand side, own-price and cross-price elasticities were calculated and used to estimate unobserved marginal costs. On the supply side, an oligopoly framework with differentiated products and Bertrand-Nash equilibrium in prices is adopted. This analysis also assumes that there is not efficiency changes by merged firms, i.e., marginal cost are the same before and after the merger. Under this assumption, mergers have significant adverse effects on consumer welfare, mainly with the increase of the prices of the products. The mergers simulation is an approach to predict post-merger prices using information about premerger market conditions, while building on assumptions about the behavior of firms and consumers. Thus, the postmergers equilibriums were simulated using the demand estimates and the recovered marginal costs. The results confirm the expected increase in prices. This result is suitable with the expectation that the mergers would implicate in increases of market prices and, without increases of economical efficiency, they can impose losses for the consumers.